Pięćdziesięciolecie gdańskiej historii wychowania - Grzybowski, Romuald (Biuletyn Historii Wychowania, 2008)
In 2009, the Faculty of the History of Science, Learning and Education, operating within the structures of the Institute of Pedagogics at Gdańsk University, will celebrate 50th anniversary of its existence. The beginnings of the Faculty and the fust years of its operation are inseparably connected with the Higher School of Pedagogics in Gdańsk, in which, in 1958 students were offered courses in pedagogics. Following these developments, a proper organizational framework was established, which was supposed to promote the development of such studies. One of the elements was the Department of History of Learning and Education, renamed - at the close of the 1960s - the Faculty of the History of Learning and Education. Since 1983 it is the Faculty of the History of Science, Learning and Education. The founder and first director of the Department, and later of the Faculty was Professor Kazimierz Kubik. Following him, it was Professor Klemens Trzebiatowski who headed the Faculty for three years. Professor Lech Mokrzecki was the subsequent director for over twenty years. Since 2005, Professor Romuald Grzybowski from Gdańsk University has been the head of the Faculty. Since the foundation of the Faculty, its employees have been conducting intensive scholarly research, originally limited to local or regional studies, and later comprising all Poland. Numerous book publications, papers and lectures delivered at scholarly conferences, form a material confirmation of intense scholarly activity by research and teaching staff of the Faculty. The scholarly conferences organized or co-organized by individual Faculty employees must be evaluated similarly. Another confirmation of the energy of the Faculty is participation of its employees in the process of education of the young ranks of scholars. The completion of ambitious tasks was possible due to such factors as stability of scholarly staff combined with their systematic replacement, good relationships between the Faculty’s employees, and, first of all, creative personality of successive directors of the Faculty. Owing to this creativity, the Faculty has not only survived, but develops intensively in all spheres of scholarly and didactic activity.